New carbon-based indigenous hollow microwave absorber / Hasnain Abdullah @ Idris - Abdullah @ Idris, Hasnain (2019)
Electromagnetic absorber has been improved from time to time and it is highly demanding for microwave absorption. However, wideband communication systems which operate at microwave frequencies required appropriate electromagnetic interference shielding to preserve signal integrity. This thesis presents a novel carbonbased indigenous hollow microwave absorber design and development with the frequency bandwidth within the 8 to 12 GHz. The main objective is to design and develop an indigenous microwave absorber with an acceptable absorption performance characteristic which is has been successfully implemented. In order to develop this absorber, the mentioned unique design and development of an indigenous microwave absorber were applied. This project examines a selected carbon-based indigenous material that is capable to absorb electromagnetic wave to investigate the effect of shape towards microwave absorption performance of the absorber. The absorber is fabricated using cardboard and indigenous carbon coated as the absorbing materials. Simulation results for the carbon-based indigenous hollow microwave absorbers shape are obtained using frequency domain in CST Microwave Studio software. The free space arch reflectivity measurement method is used to measure the hollow pyramidal microwave absorber performance. Experimental results show that the designed absorbers exhibit good absorption characteristics over a wide range of frequency. By using a new design of slotted technique was improved the performance of absorption. Result shows, a hollow indigenous microwave absorber performs a good renewal in the design of the microwave absorber. The absorbers design was measured the polarization independence absorption for both TE and TM. The results show that both polarization gives a good overview of absorption at each measurement frequency along with the simulation result. The best indigenous performance of microwave absorber can absorb more than -20 dB on the overall range of 8 to 12 GHz shows comparative to commercial. The use of cardboard as the desired form is accelerating for the construction of indigenous microwave absorber besides cost effective preparation of the measurement method according to the allowed standard has resulted in the correct and good results and can also provide the best possible absorber construction. Therefore, this project has achieved its goal.